Correlations between spectral and biophysical data obtained in canola canopy cultivated in the subtropical region of Brazil - Pinto, Daniele Gutterres; Fontana, Denise Cybis; Dalmago, Genei Antonio; Fochesatto, Elizandro; Vicari, Matheus Boni; Bremm, Carolina; da Cunha, Gilberto Rocca; de Gouvêa, Jorge Alberto; Santi, Anderson (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to identify the spectral bands, vegetation indices, and periods of the canola crop season in which the correlation between spectral data and biophysical indicators (total shoot dry matter and grain yield) is most significant. The experiment was carried out during the 2013 and 2014 crop seasons at Embrapa Trigo, in the state of Rio Grande do Sul, Brazil. A randomized complete block design was used, with four replicates, and the treatments consisted of five doses of nitrogen topdressing. Plant dry matter, grain yield, and phenology were measured. The canola spectral response was evaluated by measuring the canola canopy reflectance using a spectroradiometer, and, with this data, the SR, NDVI, EVI, SAVI, and GNDVI vegetation indices were determined. Pearson’s correlations between the spectral and biophysical variables of canola showed that the red (620 to 670 nm) and near-infrared (841 to 876 nm) bands were the best to estimate the dry matter. The vegetative period is the most indicated to obtain the most significant correlations for canola. All the used vegetation indices are adequate for estimating the dry matter and grain yield of canola.
Keywords: Brassica napus; EVI; GNDVI; NDVI; SAV; spectroradiometry